Validation of the STORM model in IRI-2001 at a high latitude station - Mansilla, Gustavo Adolfo (2009)
The International Reference Ionosphere IRI-2001 model contains geomagnetic activity dependence based on an empirical storm time ionospheric correction (STORM model). An extensive validation of the STORM model for the middle latitude region has been performed. In this paper the ability of the STORM model to predict foF2 values at high latitudes is analyzed. For this, ionosonde data obtained at Base Gral. San Martin (68.1°S, 293°E) are compared with those obtained by the IRI-2001 model with or without storm correction during four geomagnetic storms that occurred in 2000 (Rz 12 = 117) and 2001 (Rz 12 = 111). The results show that predicted values with the STORM model follow the behaviour of foF2 experimental data better than without the STORM model. The relative deviation between measured and predicted foF2 reaches values of up to 24% and 43% with and without the STORM model in IRI-2001, during the main phase of the storms. In order to explain increases of electron density that occurred prior to the storm onset and also decreases of electron density observed during the first part of the recovery of the storm, possible physical mechanisms are discussed.